Bad Debt and Cost Efficiency in Vietnamese Commercial Banks - Nguyen, Thi Hong Vinh (University of Economics Ho Chi Minh City, 2023)
The paper aims at exploring the relationship between bad debt and cost efficiency in Vietnamese commercial banks in the years 2007 – 2013. The research includes two stages: (i) Measuring the cost efficiency of banks by non-parameter Data Envelopment Analysis (DEA) method suggested by Coelli (2005); and (ii) Applying the Tobit model to identify two-way effects of bad debt and bank cost efficiency. The results show that the cost efficiency in Vietnamese commercial banks is 52.6% and there exists a direct relationship between bad debt and cost efficiency.